THE CONCEPT OF FREEDOM OF OPINION IN ISLAM AND ITS LIMITATIONS AS SEEN IN THE FACE OF CONSTITUTIONAL LAW - Al-Fitrah, Ramadhan; Siregar, Ramadhan Syahmedi; Tanjung, Dhiauddin (Jurnal Hukum dan Keadilan, 2025)
This study aims to analyze the concept of freedom of speech (Hurriyatul Ra'yi) in Islamic teachings and compare its limitations with the provisions of Indonesian Constitutional Law (UUD NRI 1945), particularly in the context of restrictions on hate speech, blasphemy, and the spread of fake news. This study uses a normative (doctrinal) legal type. We apply a philosophical-theological approach to examine Islamic Law and a juridical-normative approach to analyze the Constitutional framework. The analysis is conducted in a comparative-synchronized manner to find common ground and philosophical harmony between the two legal systems. The main primary legal materials include the Qur'an, Hadith, Fiqh Siyasah books, as well as the 1945 UUD NRI and the ITE Law. Freedom of speech in Islam is seen as a right bound by responsibilities and obligations (amar ma'ruf nahi munkar), whose main purpose is to realize the public good (maslahat) and must be stopped if it causes harm (mafsadah). These limitations are supported by the principles of ethics and prevention (Sadd al-Dzarāi'). Accordingly, the Indonesian Constitution guarantees freedom (Article 28E), but imposes mandatory restrictions through Article 28J Paragraph (2) for the sake of "religious values" and "public order." There is a strong philosophical alignment, where Islamic restrictions aimed at preventing mafsadah align with the Constitutional restrictions that protect religious values ​​and public order. Both legal systems fundamentally reject absolute and destructive freedom of expression. This synchronization forms the legal basis for the implementation of positive law (such as the ITE Law) in demanding digital accountability, which in essence protects collective ethics and morality.